Determinants of banks’ profitability and efficiency: Empirical evidence from a sample of Banking Systems - Mouna Rekik; Maha Kalai (Journal of Banking and Financial Economics, 2017)
The aim of this study is to analyze the determinants of the bank profitability and efficiency in conventional banks. This study compares accounting-based and economic-based measures of efficiency and profitability of conventional banks in fourteen countries. Accounting variables help explain cost and profit efficiency, but cost efficiency has little impact on profitability and profit efficiency. In fact, the study of profitability is crucial in assessing the health of organizations. However, profitability of the banking sector is particularly important as the soundness of the sector is closely related to the soundness of the entire economy. In this paper, banks’ profitability and its determinants in Tunisia as well as in 13 different countries were investigated. The determinants of bank profitability are analyzed with the data from 110 banks over the period 1999–2012 using the panel data method generalized method of moments. Our results suggest that researchers should probably focus more on profit efficiency than cost efficiency. Almost all banks are below the optimal size.